Multidisciplinary management of patients diagnosed with von Hippel-Lindau disease: A practical review of the literature for clinicians - Alessandro Larcher; Federico Belladelli; Giuseppe Fallara; Isaline Rowe; Umberto Capitanio; Laura Marandino; Daniele Raggi; Jody Filippo Capitanio; Michele Bailo; Rosangela Lattanzio; Costanza Barresi; Sonia Francesca Calloni; et al. (Asian Journal of Urology)
Objective: The aim of the current review is to summarize the available evidence to aid clinicians in the surveillance, treatment and follow-up of the different primary tumors developed by patients diagnosed with von Hippel-Lindau (VHL) syndrome. Methods: A non-systematic narrative review of original articles, meta-analyses, and randomized trials was conducted, including articles in the pre-clinical setting to support relevant findings. Results: VHL disease is the most common rare hereditary disorder associated with clear cell renal cell carcinoma. Affected individuals inherit a germline mutation in one VHL allele, and any somatic event that disrupt the other allele can trigger mutations, chromosomal rearrangements, or epigenetic regulations leading to oncogenesis. From a clinical perspective, patients continuously develop multiple primary tumors. Conclusion: Because VHL is considered a rare disease, very limited evidence is available for diagnosis, surveillance, active treatment with local or systemic therapy and follow-up.